The effect of Carum Carvi water extract intake as an alternative therapy for weight loss in overweight and obese women / Mahnaz Kazemipoor - Kazemipoor, Mahnaz (2014)

(untitled)
Obesity and overweight are considered as challenging health problems worldwide. Despite several modern methods for treatment of obesity such as medical nutrition therapy, low-energy diets, and physical activity. The prevalence of this disease is still high, suggesting the need for alternative therapies. One of the trending approaches is the consumption of traditional medicinal plants. Caraway (Carum carvi L.), has been traditionally used as a spice in Iran. It is also claimed as a potent medicinal plant that is used to treat a variety of ailments including obesity. The objectives of this study are to analyse the phytochemicals present in caraway water extract (CWE), to measure body composition, anthropometric indices, dietary food intake and appetite, and clinical and para-clinical parameters before and after twelve-weeks of intervention. Hence, a randomized triple blind placebo controlled clinical trial was carried out on healthy, overweight and obese adult women in Yazd, Iran. The phytochemical content of CWE was analysed using the gas chromatography-mass spectrometry (GC-MS) technique. Out of 110 volunteers registered, 70 eligible candidates were randomized into two groups of caraway treatment and placebo (N=35 in each group) and were assigned to participate in a twelve-week intervention. Data were collected through questionnaire, face-to-face interview, physical examination and biochemical tests. Body composition and anthropometric indices were measured using bioelectrical impedance analyser (BIA) and measuring tape, while the appetite index was assessed using visual analogue scale method (VAS). Participants received either 30mL/day of CWE or placebo without changing their diet or physical activity and were examined at baseline and after twelve weeks of intervention and the data were analysed using SPSS. Results showed that the predominant ingredients detected from the GC-MS analysis were of different volatile and phenolic iv compounds, including limonene, terpinene, carveol, carvone, carvacrol, and thymol. After twelve weeks of study results showed significant reduction of weight (-1.9 kg), body mass index (-0.8 kg/m2), body fat percentage (-0.7%), appetite level (-1) and carbohydrate intake (-30g) in the CWE group. All anthropometric indices including waist circumference, waist to hip ratio, thigh circumference and mid-upper arm circumference also reduced significantly (-6.2, -0.1, -5.4, and -2.2 cm respectively). Besides, significant increase was observed in the muscle percentage of the CWE group (+0.2%). No changes were detected in blood and urine tests, blood pressure and heart rate of respondents. Moreover, after twelve weeks of study, the red blood cell (RBC) level showed a clinically significant rise (+0.3 106/μL), whereas the platelet distribution width (PDW) showed a significant drop in the CWE group (-1.8 fL). The results suggest that adding CWE into the daily diet with no restriction in food intake, when combined with exercise, is of value for obese and overweight women wishing to reduce their body weight, BMI, body fat percentage, body size and appetite and carbohydrate intake. In addition, CWE intake has also improved body muscle and RBC level of the subjects with no clinical side effects. In conclusion, the results of this study suggest a safe weight loss adjuvant and a potential phytotherapeutic approach for CWE in the management of obesity.